Computational Intelligence Technique For Static Var Compensation (SVC) Installation Considering Multi-Contingencies (N-m) - Mahaletchumi, Morgan; Nor Rul Hasma, Abdullah; M. H., Sulaiman; Mahfuzah, Mustafa; Rosdiyana, Samad (2015)

(untitled)
This paper discusses about a new approach based on Evolutionary Programming (EP) optimization technique for installation SVC considering multi-contingencies (N-m) which occurred in the power system. The proposed technique determines the optimum sizing in order to reduce the total transmission loss in the system and this would be the objective function of the transmissions system network. In addition, Static Voltage stability Index (SVSI) was used as tool to indicate the location that to be installed into the system. A computer program was written in MATLAB. The design program tested on IEEE 30 Bus-RTS. Finally, comparatives studies made between EP and Artificial Immune System (AIS).